PENGEMBANGAN SISTEM INFORMASI BERBASIS ANDROID UNTUK MENINGKATKAN PELAYANAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL - Adam Firmansyah; Vinna Agustina; Nana Siti Nurjanah; Tati Suprapti (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
The Department of Population and Civil Registration is one of the public service institutions that includes recording and publishing services that aim to record data from each resident as completely as possible and therefore provide true certainty about events or events that have been experienced by residents. Meanwhile, the services provided by the Department of Population and Civil Registration are birth certificates for babies aged 0-60 days, making Family Cards (KK) and printing e-KTPs which are currently busy in Indonesia.